STRATEGI PEMBELAJARAN MANDIRI MENGGUNAKAN MODUL DAN TATAP MUKA TERBATAS DI KABUPATEN POSO - Frans Andilemba Tadanugi (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2021)
The Covid-19 pandemic requires teacher creativity and innovation in designing learning so that students can still learn from home. This study aims to describe the use of independent learning strategies by using modules as a learning resource for students with a combination of visiting teachers (limited face-to-face) every week. This study is a descriptive study that took the research subjects of class VII students of SMP Negeri 3 Lage which consisted of 70 students who were divided into 6 small groups based on where they lived. The steps of this research are planning, implementation, obstacles faced, problem-solving. Learning from home with limited modules and face-to-face can take place well, students are enthusiastic about learning even though learning facilities are limited. Thus, it can be said that independent learning strategies with limited modules and face-to-face can be applied to the Covid-19 pandemic situation.